Integrated assessment of resource-energy-environment nexus in China's iron and steel industry. (20th September 2019) - Zhang, Shaohui; Yi, Bo-Wen; Worrell, Ernst; Wagner, Fabian; Crijns-Graus, Wina; Purohit, Pallav; Wada, Yoshihide; Varis, Olli
Abstract: MESSAGEix model are widely used for forecasting long-term energy consumption and emissions, as well as modelling the possible GHGs mitigations. However, because of the complexity of manufacturing sectors, the MESSAGEix model aggregate detailed technology options and thereby miss linkages across sub-sectors, which leads to energy saving potentials are often not very realistic and cannot be used to design specific policies. Here, we integrate Material/Energy/water Flow Analysis (MEWFA) and nexus approach into the MESSAGEix to estimate resource-energy-environment nexus in China's iron and steel industry. Results show that between 2010 and 2050 energy efficiency measures and route shifting of China's steel industry will decrease raw material input by 14%, energy use by 7%, water consumption by 8%, CO2 emissions by 7%, NOx emissions by 9%, and SO2 emissions by 14%, respectively. However, water withdrawal and PM2.5 emissions will increase by 14% and 20%, respectively. The main reason is that water withdrawal and PM2.5 emissions in the process of BF-BOF are over 4 times lower than the process scrap-EAF. Therefore, policy makers should consider nexus effects when design integrated policy to achieve multiple targets. Finally, future directions on enhancing the representation of manufacturing sectors in IAMs are given. Highlights: A new approach for manufacturing sectors in MESSAGEix model is developed. Resource-Energy-Environment Nexus in China's iron and steel industry are quantified. Energy efficiency would lead to large reductions of material, water, and emission. Industrial characteristics should be modelled in long-term energy system models.